2005
DOI: 10.1097/00004356-200509000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of adolescents and young adults 10 years after serious traumatic brain injury

Abstract: The aim of this study was to investigate health-related quality of life (HRQoL) in a population-based group of young adults with serious traumatic brain injury (TBI) acquired 10 years earlier. In the time period 1987--1991, all 165 residents (<18 years of age) in the south-western health care region of Sweden who had suffered a serious TBI were followed up. Of these, 109 (67%) participated in this follow-up study, which was conducted using the 15-dimension (15D) HRQoL instrument. Their HRQoL was compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 20 publications
2
26
3
1
Order By: Relevance
“…The traceable individuals (149) were invited to take part in a follow-up investigation. Of the traceable individuals, 109 answered a quality-of-life questionnaire [20]. Another 20 did not answer and 16 did not wish to participate, two individuals had died and two had moved abroad.…”
Section: Subjectsmentioning
confidence: 99%
“…The traceable individuals (149) were invited to take part in a follow-up investigation. Of the traceable individuals, 109 answered a quality-of-life questionnaire [20]. Another 20 did not answer and 16 did not wish to participate, two individuals had died and two had moved abroad.…”
Section: Subjectsmentioning
confidence: 99%
“…Although Horneman et al (2005) reported lower HRQOL in a severe TBI group 10 years postinjury compared with that of a matched control group, 80% of the TBI patients had not received any rehabilitation services. Moreover, 23.0% of these patients received no follow-up after discharge from acute care.…”
Section: Health-related Quality Of Life and Characteristics Of The Enmentioning
confidence: 77%
“…The SF-36 subscales of vitality (energy and fatigue) and bodily pain were the operational measures most frequently used for symptoms. Only four of the studies (Cantor et al, 2008;Chiu et al, 2006;Horneman et al, 2005;McCauley et al, 2005) assessed depression in TBI survivors.…”
Section: Functional Status and Symptomsmentioning
confidence: 99%
“…The intellectual complaints included difficulties with learning, memory, intellectual functioning and slowness of thinking (Klonoff, Clarc & Klonoff, 1993). Quality of life has been found to be negatively affected 10 years or longer after injury (Horneman et al, 2005;Cattelani et al, 1998). For a group of 124 persons, 14 years after CTBI, difficulties were reported to have persisted into adulthood.…”
Section: Longterm Cognitive Outcomementioning
confidence: 99%